The cell for electron irradiation of stressed steel samples in a supercritical water flow for corrosion evaluation - Bakai, A.S.; Boriskin, V.N.; Bratchenko, M.I.; Dronov, R.N.; Dyuldya, S.V.; Gorenko, Yu.V.; Shelepko, S.V. (Вопросы атомной науки и техники, 2019)
To study experimentally the stress enhanced corrosion of structural materials in a water coolant flow under electron irradiation, a novel design of the target irradiation cell was developed. The stress application scheme is described and the stress-strain state of samples is calculated. Hydraulic resistance of the stainless steel 12X18H10T samples loaded cell has been measured at a dedicated facility and is discussed in terms of hydraulic and hydrodynamic models. System Thermal Hydraulics calculations have shown the device capability to operate efficiently in a natural convection driven Supercritical Water Circulation Loop.